RETRACTED: Study of empirical mechanisms for organizing interaction in a multi-level innovation environment with information asymmetry - Makhosheva Salima; Gurtuev Alim; Ivanov Zaur (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001